2021
DOI: 10.1007/s10903-021-01152-4
|View full text |Cite
|
Sign up to set email alerts
|

Refugee and Migrant Health Literacy Interventions in High-Income Countries: A Systematic Review

Abstract: Health literacy is a key determinant of health in refugee and migrant populations living in in high-income countries (HICs). We conducted a systematic review of randomized-controlled trials (RCTs) to characterize the scope, methodology, and outcomes of research on interventions aimed at improving health literacy among these vulnerable populations. We searched EMBASE, MEDLINE, PsycINFO, CINAHL, and Web of Science databases to identify RCTs of health literacy intervenions in our target population published betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…9,16 There are limited numbers of published studies regarding providing health literacy education for refugees. 17 A systematic review of 23 randomized controlled trials found heterogeneity regarding areas of educational focus and countries of participant origin.…”
Section: Discussionmentioning
confidence: 99%
“…9,16 There are limited numbers of published studies regarding providing health literacy education for refugees. 17 A systematic review of 23 randomized controlled trials found heterogeneity regarding areas of educational focus and countries of participant origin.…”
Section: Discussionmentioning
confidence: 99%
“… 51 Revealing the challenges of the migrant workers is only the first step to promote preventive behaviors and reduce the risk of these vulnerable people. Effective interventions for health literacy could improve health issues of migrant populations, 52 and tailored communicative technologies are expected to empower migrant workers to stay informed, sustain preventive behaviors, and improve communication for both information seekers and healthcare providers. 53 , 54 More specifically, the multi-media content could help grow individual's knowledge and self-care skills and empower them to be active in their care.…”
Section: Discussionmentioning
confidence: 99%
“…The previous section on the health of refugees notes the precarious conditions in which refugee populations may find themselves, even in the final host country and after formal recognition of their refugee status. As determinants of health, improvements in the physical environment will prevent the spread of communicable diseases, and education, literacy, social support and coping behaviour will all contribute to the inclusion of these populations in the host country's society (Fox et al, 2022). Perhaps the most important element is employment and working conditions.…”
Section: Social Determinants Of Healthmentioning
confidence: 99%
“…These main determinants are: Income and social status. Employment and working conditions. Education and literacy. Childhood experiences. Physical environments. Social supports and coping skills. Healthy behaviours. Access to health services. The previous section on the health of refugees notes the precarious conditions in which refugee populations may find themselves, even in the final host country and after formal recognition of their refugee status. As determinants of health, improvements in the physical environment will prevent the spread of communicable diseases, and education, literacy, social support and coping behaviour will all contribute to the inclusion of these populations in the host country’s society (Fox et al, 2022).…”
Section: Social Determinants Of Healthmentioning
confidence: 99%